Iron-silicon-aluminum magnetic powder core and preparation method thereof
Spherical FeSiAl powder is prepared by aerosolizing powder on 200 mesh sieve, and combined with mechanical crushing and insulating coating technology, the problem of underutilization of powder in the ferrosilicon aluminum magnetic powder core is solved, and the performance and resource utilization of the magnetic powder core are improved. , reduces costs.
Patent Information
- Application Number
- CN202411396104.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-31
AI Technical Summary
During the preparation process of existing ferrosilicon aluminum magnetic powder cores, the powder under 200 mesh screen cannot be fully utilized, resulting in waste of resources and increased costs.
Spherical FeSiAl powder is prepared by aerosolizing 200 mesh sieve powder, and it is mechanically crushed and passed through a 200 mesh screen. Combined with insulating coating, press forming and stress annealing, a ferrosilicon aluminum magnetic powder core with smooth surface without sharp corners is prepared. .
The high saturation flux density, high magnetic permeability and low loss performance of the ferrosilicon aluminum magnetic powder core are improved, and the aerosolized powder is effectively utilized to reduce the cost of raw materials.
Smart Images

Figure CN119230235A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic materials, and in particular to a Sendust magnetic powder core and a preparation method thereof. Background Art
[0002] As a functional material, magnetic powder cores are increasingly widely used in power electronic equipment and devices. With the rapid development of electronic power and information industries, lightweight, high frequency and high current have become development trends, requiring magnetic powder cores to have high saturation flux density, high magnetic permeability, low loss and good temperature stability. Sendust aluminum powder is a commonly used raw material for magnetic powder cores. There are two main methods for its preparation: aerosolization and mechanical crushing. The FeSiAl powder prepared by aerosolization is spherical, easy to insulate and coat, and has excellent comprehensive performance. The mechanical crushing method crushes the alloy ingot to obtain powder. The powder has an irregular shape and obvious sharp corners. During the pressing process, the sharp corners can easily pierce the coating layer, resulting in increased losses. However, compared with aerosol powder, the powder prepared by mechanical crushing has the advantages of simple process, low cost and high mechanical strength.
[0003] As the particle size of Sendust powder decreases, the loss of Sendust magnetic powder core shows a decreasing trend, so the Sendust magnetic powder core on the market usually uses powder under 200 mesh sieve, and its D50 is between 30-40μm. For atomized Sendust powder, the mass proportion under 200 mesh sieve is usually 65%-75%, which means that about 30% of the powder cannot be effectively used, resulting in waste of resources and increased costs. Summary of the invention
[0004] The invention provides a sendust magnetic powder core and a preparation method thereof, which are used to solve the defect that raw material powder cannot be fully and effectively utilized in the preparation process of the sendust magnetic powder core in the prior art.
[0005] According to a first aspect of the present invention, the present invention provides a sendust magnetic powder core; the sendust magnetic powder core is prepared from a raw material including spherical FeSiAl powder, the spherical FeSiAl powder is prepared by atomizing a 200-mesh sieve powder; the composition of the spherical FeSiAl powder is Fe 100-a-b Si a Al b , wherein 8.5≤a≤9.9, 5.0≤b≤6.0, a and b respectively represent the mass percentage of the corresponding components; the grain size of the spherical FeSiAl powder is 10-30 μm.
[0006] Furthermore, the spherical FeSiAl powder is formed by a number of polyhedral grains similar to pomegranate seeds that are tightly combined, and the cross section is smooth without sharp corners.
[0007] Furthermore, the raw materials for preparation also include spherical FeSiAl powder, wherein the spherical FeSiAl powder is atomized powder under a 200-mesh sieve, and D50 is 30-40 μm; Preferably, the composition of the spherical FeSiAl powder is consistent with the composition of the quasi-spherical FeSiAl powder.
[0008] Furthermore, the amount of the quasi-spherical FeSiAl powder is 30%-50% of the sum of the amounts of the quasi-spherical FeSiAl powder and the spherical FeSiAl powder.
[0009] Furthermore, the magnetic core density of the Sendust magnetic powder core is 5.9-6.25 g / cm 3 ; The magnetic permeability of the Sendust magnetic powder core is 59-62.
[0010] According to the second aspect of the present invention, the present invention also provides a Sendust magnetic powder core, which is prepared from a raw material including quasi-spherical FeSiAl powder, and the quasi-spherical FeSiAl powder is formed by a number of polyhedral grains similar to pomegranate seeds that are tightly combined, and the cross-section is smooth without sharp corners.
[0011] Furthermore, the spherical FeSiAl powder is prepared by atomizing powder on a 200-mesh sieve; the composition of the spherical FeSiAl powder is Fe 100-a-b Si a Al b , wherein 8.5≤a≤9.9, 5.0≤b≤6.0, a and b respectively represent the mass percentage of the corresponding components; the grain size of the spherical FeSiAl powder is 10-30μm.
[0012] Furthermore, the raw materials for preparation also include spherical FeSiAl powder, wherein the spherical FeSiAl powder is atomized powder under a 200-mesh sieve, and D50 is 30-40 μm; Preferably, the composition of the spherical FeSiAl powder is consistent with the composition of the quasi-spherical FeSiAl powder.
[0013] Furthermore, the amount of the quasi-spherical FeSiAl powder is 30%-50% of the sum of the amounts of the quasi-spherical FeSiAl powder and the spherical FeSiAl powder.
[0014] Furthermore, the magnetic core density of the Sendust magnetic powder core is 5.90-6.25 g / cm 3 ; The magnetic permeability of the Sendust magnetic powder core is 58-62H / m.
[0015] According to a third aspect of the present invention, the present invention also provides a method for preparing the above-mentioned Sendust magnetic powder core, comprising the following steps: The powder on the atomized 200-mesh sieve is mechanically crushed and passed through a 200-mesh sieve to obtain spherical FeSiAl powder; The obtained quasi-spherical FeSiAl powder is subjected to insulation coating, compression molding and stress annealing in sequence to obtain a Sendust magnetic powder core.
[0016] Furthermore, the insulating coating comprises: uniformly mixing the quasi-spherical FeSiAl powder with a mixed solution comprising phosphoric acid, silicone resin and an organic solvent and then drying the mixed solution to obtain the quasi-spherical FeSiAl insulating powder.
[0017] Preferably, in the mixed solution, the weight ratio of phosphoric acid, silicone resin and organic solvent is (0.5-1): (0.2-0.5): (2-3).
[0018] Preferably, the mass percentage of the quasi-spherical FeSiAl powder to the total mass of the quasi-spherical FeSiAl powder and the mixed liquid is 94%-96.5%.
[0019] Preferably, the spherical FeSiAl insulating powder obtained after insulation coating is mixed evenly with a demoulding lubricant and then pressed into shape; more preferably, the amount of the demoulding lubricant is 0.2%-0.4% of the amount of the spherical FeSiAl insulating powder.
[0020] Furthermore, the Sendust magnetic powder core further comprises spherical FeSiAl powder, and the insulating coating comprises: uniformly mixing the quasi-spherical FeSiAl powder with a mixed solution comprising phosphoric acid, silicone resin and an organic solvent, and then drying to obtain quasi-spherical FeSiAl insulating powder; uniformly mixing the spherical FeSiAl powder with a mixed solution comprising phosphoric acid, silicone resin and an organic solvent, and then drying to obtain spherical FeSiAl insulating powder; Preferably, the mass percentage of the quasi-spherical FeSiAl powder to the total mass of the quasi-spherical FeSiAl powder and the mixed liquid is 94%-96.5%; the mass percentage of the spherical FeSiAl powder to the total mass of the spherical FeSiAl powder and the mixed liquid is 94%-96.5%; Preferably, the quasi-spherical FeSiAl insulating powder obtained after insulation coating and the spherical FeSiAl insulating powder are mixed evenly with a demolding lubricant and then pressed into shape; more preferably, the amount of the demolding lubricant is 0.2%-0.4% of the sum of the amounts of the quasi-spherical FeSiAl insulating powder and the spherical FeSiAl insulating powder.
[0021] Furthermore, the pressing force of the pressing molding is 20-22 t / cm 2 The outer diameter of the pressed magnetic powder core is 25-30mm, the inner diameter is 14-15mm, and the height is 10-12mm.
[0022] Furthermore, the stress annealing is performed at a temperature of 600-800° C. and for a time of 30-50 min.
[0023] The present invention provides a sendust magnetic powder core prepared from a raw material including spherical FeSiAl powder of a specific grain size and a specific composition. Compared with conventional mechanically crushed sendust magnetic powder on the market, the spherical FeSiAl powder of the present invention has a smooth cross section without sharp corners and a more uniform coating layer. Such a structure can ensure that the sendust magnetic powder core has high saturation magnetic flux density, high magnetic permeability, low loss and other properties. In addition, the spherical FeSiAl powder is prepared from powder on a 200-mesh sieve by gas atomization, so that the powder on the 200-mesh sieve by gas atomization can be effectively utilized, reducing the cost of the raw materials of the powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is one of the SEM images of the spherical FeSiAl powder in the Sendust magnetic powder core provided in Example 1 of the present invention.
[0026] Figure 2 This is the second SEM image of the spherical FeSiAl powder in the Sendust magnetic powder core provided in Example 1 of the present invention.
[0027] Figure 3 This is the third SEM image of the spherical FeSiAl powder in the Sendust magnetic powder core provided in Example 1 of the present invention.
[0028] Figure 4 This is a SEM image of a Sendust magnetic powder core provided in Example 4 of the present invention.
[0029] Figure 5 It is a SEM picture of atomized spherical FeSiAl powder and FeSiAl mechanically crushed powder in a sendustine magnetic powder core provided in Comparative Examples 1 and 2 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Aiming at the defect that the raw material powder, especially the powder under 200 mesh sieve, cannot be fully and effectively utilized in the existing preparation process of sendust magnetic powder core, in a first typical embodiment of the present invention, the present invention provides a sendust magnetic powder core. According to some specific embodiments of the present invention, the sendust magnetic powder core is prepared from a raw material including spherical FeSiAl powder, and the spherical FeSiAl powder is prepared by atomizing the powder on 200 mesh sieve; the composition of the spherical FeSiAl powder is Fe 100-a-b Si a Al b , wherein 8.5≤a≤9.9, 5.0≤b≤6.0, a and b represent the mass percentage of the corresponding components respectively; the grain size of the spherical FeSiAl powder is 10-30μm.
[0032] It should be noted that the grain size refers to the size of the smallest microstructure of the spherical FeSiAl powder.
[0033] In the above scheme, the sendust magnetic powder core of the present invention is prepared from raw materials including spherical FeSiAl powder of specific grain size and specific composition, so that the surface of the sendust magnetic powder core obtained is smooth without sharp corners, and such a structure can ensure that the sendust magnetic powder core has high saturation magnetic flux density, high magnetic permeability, low loss and other properties. In addition, the spherical FeSiAl powder is prepared from the powder on the atomized 200 mesh sieve, so that the powder on the atomized 200 mesh sieve can be effectively utilized, reducing the cost of the powder raw materials.
[0034] According to some specific embodiments of the present invention, the spherical FeSiAl powder is formed by a number of polyhedral grains similar to pomegranate seeds that are tightly combined, and the surface of the spherical FeSiAl powder is smooth without sharp corners.
[0035] In the above scheme, the quasi-spherical FeSiAl powder is in the shape of a pomegranate, which is formed by a number of polyhedral grains similar to pomegranate seeds tightly combined. The surface of the polyhedral grains is smooth without obvious edges and corners. The quasi-spherical FeSiAl powder of such a shape is used to prepare the iron silicon aluminum magnetic powder core. It is not easy to puncture the coating layer during the pressing process, which can effectively avoid the increase of loss.
[0036] According to some specific embodiments of the present invention, the raw materials for preparation further include spherical FeSiAl powder, and the spherical FeSiAl powder is atomized powder under a 200-mesh sieve, and D50 is 30-40 μm.
[0037] In the above scheme, the raw materials also include spherical FeSiAl powder, and the size of the spherical FeSiAl powder is limited, which can further effectively increase the magnetic flux density and magnetic permeability of the Sendust magnetic powder core and reduce the loss.
[0038] According to some specific embodiments of the present invention, the composition of the spherical FeSiAl powder is consistent with the composition of the quasi-spherical FeSiAl powder.
[0039] According to some specific embodiments of the present invention, the amount of quasi-spherical FeSiAl powder is 30%-50% of the sum of the amounts of quasi-spherical FeSiAl powder and spherical FeSiAl powder.
[0040] Optionally, the amount of quasi-spherical FeSiAl powder is 30%, 35%, 40%, 45% or 50% of the sum of the amounts of quasi-spherical FeSiAl powder and spherical FeSiAl powder.
[0041] In the above scheme, by limiting the mass percentage of the amount of quasi-spherical FeSiAl powder to the sum of the amounts of quasi-spherical FeSiAl powder and spherical FeSiAl powder to a reasonable range, the sendustine aluminum magnetic powder core can be ensured to have high saturation magnetic flux density, high magnetic permeability, low loss and other properties on the basis of reducing the cost of raw materials.
[0042] According to some specific embodiments of the present invention, the core density of the Sendust magnetic powder core is 5.9-6.25 g / cm 3 ;The magnetic permeability of Sendust magnetic powder core is 59-62.
[0043] In a second typical embodiment of the present invention, the present invention provides a sendust magnetic powder core. According to some specific embodiments of the present invention, the sendust magnetic powder core is prepared from a raw material including quasi-spherical FeSiAl powder, wherein the quasi-spherical FeSiAl powder is formed by a number of polyhedral grains similar to pomegranate seeds that are tightly combined, and the cross-section is smooth without sharp corners.
[0044] According to some specific embodiments of the present invention, the spherical FeSiAl powder is prepared by atomizing powder on a 200-mesh sieve; the composition of the spherical FeSiAl powder is Fe 100-a-b Si a Al b , wherein 8.5≤a≤9.9, 5.0≤b≤6.0, a and b respectively represent the mass percentage of the corresponding components; the grain size of the spherical FeSiAl powder is 10-30μm.
[0045] According to some specific embodiments of the present invention, the raw materials for preparation further include spherical FeSiAl powder, and the spherical FeSiAl powder is atomized powder under a 200-mesh sieve, and D50 is 30-40 μm.
[0046] According to some specific embodiments of the present invention, the composition of the spherical FeSiAl powder is consistent with the composition of the quasi-spherical FeSiAl powder.
[0047] According to some specific embodiments of the present invention, the amount of the quasi-spherical FeSiAl powder is 30%-50% of the sum of the amounts of the quasi-spherical FeSiAl powder and the spherical FeSiAl powder.
[0048] According to some specific embodiments of the present invention, the core density of the Sendust magnetic powder core is 5.90-6.25 g / cm 3 ; The magnetic permeability of the Sendust magnetic powder core is 58-62H / m.
[0049] In a third typical embodiment of the present invention, the present invention also provides a method for preparing the above-mentioned Sendust magnetic powder core, comprising the following steps: The powder on the atomized 200-mesh sieve is mechanically crushed and passed through a 200-mesh sieve to obtain spherical FeSiAl powder; The obtained spherical FeSiAl powder is subjected to insulation coating, compression molding and stress annealing in sequence to obtain a Sendust magnetic powder core.
[0050] In the above scheme, the powder on the aerosolized 200-mesh sieve is first crushed by mechanical crushing, and then passed through a 200-mesh sieve to obtain an ideal spherical FeSiAl powder, and then successively subjected to insulation coating, pressing and stress annealing to obtain an iron silicon aluminum magnetic powder core. The preparation method is simple and suitable for wide promotion.
[0051] According to some specific embodiments of the present invention, the insulating coating comprises: uniformly mixing spherical FeSiAl powder with a mixed solution comprising phosphoric acid, silicone resin and an organic solvent and then drying to obtain spherical FeSiAl insulating powder. The organic solvent is one of ethanol, acetone and ethyl acetate.
[0052] In the above scheme, the spherical FeSiAl powder is surface treated by phosphoric acid insulation coating to form a phosphate coating on the surface of the spherical FeSiAl powder, which has insulation, corrosion resistance, improved fluidity and enhanced mechanical properties. Silicone resin is a polymer compound with good heat resistance, electrical insulation, weather resistance and chemical stability. The spherical FeSiAl powder is combined with silicone resin to improve insulation, mechanical properties, thermal stability, corrosion resistance, processing performance, environmental adaptability and molding efficiency.
[0053] According to some specific embodiments of the present invention, the mass percentage of the spherical FeSiAl powder to the total mass of the spherical FeSiAl powder and the mixed liquid is 94%-96.5%.
[0054] Optionally, the mass percentage of the spherical FeSiAl powder to the total mass of the mixed solution including the spherical FeSiAl powder and phosphoric acid, silicone resin and organic solvent can be 94%, 94.5%, 95%, 95.5%, 96% or 96.5%, etc.
[0055] In the above scheme, by limiting the mass percentage of the quasi-spherical FeSiAl powder to the total mass of the quasi-spherical FeSiAl powder and the mixed liquid to a reasonable range, it is more conducive to improving the phosphoric acid insulation coating efficiency.
[0056] According to some specific embodiments of the present invention, the spherical FeSiAl insulating powder obtained after the insulating coating is mixed evenly with a demoulding lubricant and then pressed into shape.
[0057] In the above scheme, before pressing and molding, the spherical FeSiAl insulating powder is evenly mixed with a demoulding lubricant, which can improve powder fluidity, prevent powder aggregation, reduce pressing force, improve molding quality, and facilitate demoulding and protect the mold.
[0058] According to some specific embodiments of the present invention, the amount of the demoulding lubricant used is 0.2%-0.4% of the amount of the spherical FeSiAl insulating powder used.
[0059] Optionally, the amount of the demoulding lubricant used can be 0.2%, 0.25%, 0.3%, 0.35% or 0.4% of the amount of the spherical FeSiAl insulating powder used.
[0060] In the above scheme, the amount of demoulding lubricant added is precisely controlled to ensure that the magnetic properties of the powder are not affected and a good molding effect can be achieved.
[0061] According to some specific embodiments of the present invention, the sendust magnetic powder core also includes spherical FeSiAl powder, and the insulating coating includes: uniformly mixing the quasi-spherical FeSiAl powder with a mixed solution including phosphoric acid, silicone resin and an organic solvent, and then drying to obtain quasi-spherical FeSiAl insulating powder; uniformly mixing the spherical FeSiAl powder with a mixed solution including phosphoric acid, silicone resin and an organic solvent, and then drying to obtain spherical FeSiAl insulating powder.
[0062] In the above scheme, phosphoric acid insulation coating is used to treat the surface of FeSiAl powder, so as to form a phosphate coating on the surface of FeSiAl powder, which has insulation, corrosion resistance, improved fluidity and enhanced mechanical properties. Silicone resin is a polymer compound with good heat resistance, electrical insulation, weather resistance and chemical stability. Combining FeSiAl powder with silicone resin can improve insulation, mechanical properties, thermal stability, corrosion resistance, processing performance, environmental adaptability and molding efficiency.
[0063] According to some specific embodiments of the present invention, the mass percentage of quasi-spherical FeSiAl powder in the total mass of the quasi-spherical FeSiAl powder and the mixed liquid is 94%-96.5%; the mass percentage of spherical FeSiAl powder in the total mass of the spherical FeSiAl powder and the mixed liquid is 94%-96.5%.
[0064] Optionally, the mass percentage of quasi-spherical FeSiAl powder in the total mass of quasi-spherical FeSiAl powder and the mixed liquid can be 94%, 94.5%, 95%, 95.5%, 96% or 96.5%, etc.; the mass percentage of spherical FeSiAl powder in the total mass of spherical FeSiAl powder and the mixed liquid can be 94%, 94.5%, 95%, 95.5%, 96% or 96.5%, etc.
[0065] According to some specific embodiments of the present invention, the quasi-spherical FeSiAl insulating powder obtained after the insulating coating and the spherical FeSiAl insulating powder are mixed evenly with a demoulding lubricant and then pressed into shape.
[0066] In the above scheme, before pressing and molding, the quasi-spherical FeSiAl insulating powder, the spherical FeSiAl insulating powder and the demoulding lubricant are evenly mixed, which can improve the powder fluidity, prevent powder aggregation, reduce the pressing force, improve the molding quality, and facilitate demoulding and protect the mold.
[0067] According to some specific embodiments of the present invention, the amount of the demoulding lubricant is 0.2%-0.4% of the sum of the amounts of the quasi-spherical FeSiAl insulating powder and the spherical FeSiAl insulating powder.
[0068] Optionally, the amount of the demoulding lubricant can be 0.2%, 0.25%, 0.3%, 0.35% or 0.4% of the sum of the amounts of the quasi-spherical FeSiAl insulating powder and the spherical FeSiAl insulating powder.
[0069] In the above scheme, the amount of demoulding lubricant added is precisely controlled to ensure that the magnetic properties of the powder are not affected and a good molding effect can be achieved.
[0070] According to some specific embodiments of the present invention, the pressing force of the pressing molding is 20-22 t / cm 2 The outer diameter of the magnetic powder core after pressing is 25-30 mm, the inner diameter is 14-15 mm, and the height is 10-12 mm. Preferably, the outer diameter of the magnetic powder core after pressing is 26-27 mm, the inner diameter is 14-15 mm, and the height is 11.0-11.2 mm. More preferably, the outer diameter of the magnetic powder core after pressing is 26.9 mm, the inner diameter is 14.7 mm, and the height is 11.0-11.2 mm.
[0071] In the above scheme, by limiting the pressing force of the pressing molding within a reasonable range, it can be ensured that the magnetic powder core meets the quality and performance requirements. By limiting the outer diameter, inner diameter and height of the magnetic powder core after pressing molding within a reasonable range, it can be adapted to specific applications.
[0072] According to some specific embodiments of the present invention, the stress annealing is performed at a temperature of 600-800° C. and for a time of 30-50 min.
[0073] Optionally, the stress annealing temperature may be 600° C., 650° C., 700° C., 750° C. or 800° C., etc., and the stress annealing time may be 30 min, 35 min, 40 min, 45 min or 50 min, etc.
[0074] In the above scheme, by limiting the temperature and time of stress annealing within a reasonable range, it is more conducive to removing the stress of the magnetic powder core and improving the performance of the Sendust magnetic powder core.
[0075] In the following examples and comparative examples, in the mixed solution including phosphoric acid, silicone resin and organic solvent, the weight ratio of phosphoric acid, silicone resin and organic solvent is 2:1:10.
[0076] Example 1
[0077] This embodiment provides a sendust magnetic powder core, which is prepared from spherical FeSiAl powder. Figure 1 , Figure 2 and Figure 3 As shown in the figure, the spherical FeSiAl powder is an irregular polyhedron of pomegranate seeds. The composition of the spherical FeSiAl powder is Fe 100-a- b Si a Al b , where a=8.8, b=5.4; the grain size of the spherical FeSiAl powder is 10-30μm.
[0078] The preparation method of Sendust magnetic powder core is as follows: The powder on the atomized 200-mesh sieve was mechanically crushed by a WQ-80 air flow mill and then passed through a 200-mesh sieve to obtain spherical FeSiAl powder.
[0079] The obtained quasi-spherical FeSiAl powder is mixed evenly with a mixed solution including phosphoric acid, organic silicon resin and organic solvent, and then dried to obtain quasi-spherical FeSiAl insulating powder. The mass percentage of the quasi-spherical FeSiAl powder in the total mass of the quasi-spherical FeSiAl powder and the mixed solution is 94%.
[0080] The Sendust magnetic powder core is obtained by sequentially performing insulation coating, pressing molding and stress annealing.
[0081] The spherical FeSiAl insulation powder obtained after insulation coating is mixed with the demoulding lubricant and then pressed into shape; the amount of demoulding lubricant used is 0.4% of the amount of spherical FeSiAl insulation powder used. The pressing force for pressing is 20t / cm 2 The outer diameter of the pressed magnetic powder core is 26.9 mm, the inner diameter is 14.7 mm, and the height is 11.2 mm.
[0082] After pressing and forming, the magnetic powder core is subjected to stress relief annealing at a temperature of 700°C for 40 minutes to obtain a Sendust magnetic powder core, and the magnetic core performance is tested.
[0083] Example 2
[0084] This embodiment provides a sendust magnetic powder core, which is different from the embodiment 1 in that: in the preparation method of the sendust magnetic powder core, the pressing force of the pressing molding is 22t / cm 2 .
[0085] Example 3
[0086] The present embodiment provides a sendust magnetic powder core, which is prepared from raw materials including quasi-spherical FeSiAl powder and spherical FeSiAl powder, wherein the quasi-spherical FeSiAl powder is the same as that in Example 1, and the spherical FeSiAl powder is atomized spherical FeSiAl powder, and its composition is consistent with that of the quasi-spherical FeSiAl powder, and the D50 of the spherical FeSiAl powder is 35 μm.
[0087] The preparation method of Sendust magnetic powder core is as follows: The powder on the atomized 200-mesh sieve is mechanically crushed and passed through a 200-mesh sieve to obtain spherical FeSiAl powder.
[0088] The quasi-spherical FeSiAl powder is uniformly mixed with a mixed solution including phosphoric acid, silicone resin and organic solvent, and then dried to obtain a quasi-spherical FeSiAl insulating powder, wherein the mass percentage of the quasi-spherical FeSiAl powder to the total mass of the quasi-spherical FeSiAl powder and the mixed solution is 96%; the spherical FeSiAl powder under an atomized 200-mesh sieve is uniformly mixed with a silicone resin, and then dried to obtain a spherical FeSiAl insulating powder, wherein the mass percentage of the spherical FeSiAl powder to the total mass of the spherical FeSiAl powder and the mixed solution is 95%.
[0089] The spherical FeSiAl insulating powder and the spherical FeSiAl insulating powder are mixed evenly in a ratio of 5:5, and then mixed evenly with a demoulding lubricant accounting for 0.4% of the insulating powder mass ratio, and pressed into a magnetic powder core with a pressing force of 20t / cm 2 The dimensions of the magnetic powder core are 26.9mm in outer diameter, 14.7mm in inner diameter and 11.2mm in height.
[0090] After pressing and forming, the magnetic powder core is subjected to stress relief annealing at a temperature of 700°C for 40 minutes to obtain a Sendust magnetic powder core, and the magnetic core performance is tested.
[0091] Example 4
[0092] This embodiment provides a sendust magnetic powder core, which is different from the embodiment 3 in that, during the preparation of the sendust magnetic powder core, the spherical FeSiAl insulating powder and the spherical FeSiAl insulating powder are mixed in a ratio of 3:7; the pressing force is 22 t / cm 2 .like Figure 4 As shown, the surface of the Sendust magnetic powder core is smooth and has no sharp corners.
[0093] Comparative Example 1
[0094] This comparative example provides a sendust magnetic powder core, which is prepared from the atomized spherical FeSiAl powder of Example 3. Figure 5 As shown in (a), the gas atomized spherical FeSiAl powder is spherical with a D50 of 30-40μm.
[0095] The preparation method of Sendust magnetic powder core is as follows: The powder under the atomized 200 mesh sieve is uniformly mixed with the silicone resin and then dried to obtain spherical FeSiAl insulating powder. The mass percentage of the spherical FeSiAl powder in the total mass of the mixed liquid including the spherical FeSiAl powder and phosphoric acid, the silicone resin and the organic solvent is 94%.
[0096] The spherical FeSiAl insulating powder obtained after insulation coating is mixed with the demoulding lubricant and then pressed into shape; the amount of demoulding lubricant used is 0.4% of the amount of spherical FeSiAl insulating powder used. The pressing force of pressing is 20t / cm2 The outer diameter of the pressed magnetic powder core is 26.9 mm, the inner diameter is 14.7 mm, and the height is 11.2 mm.
[0097] After pressing and forming, the magnetic powder core is subjected to stress relief annealing at a temperature of 700°C for 40 minutes to obtain a Sendust magnetic powder core, and the magnetic core performance is tested.
[0098] Comparative Example 2
[0099] This comparative example provides a FeSiAl magnetic powder core, which is prepared from 200 mesh FeSiAl mechanically crushed powder purchased from the market. Figure 5 As shown in (b), the surface of the FeSiAl mechanically crushed powder is not smooth and has sharp corners.
[0100] The preparation method of Sendust magnetic powder core is as follows: The -200 mesh FeSiAl mechanical crushing powder purchased from the market is mixed evenly with a mixed solution including phosphoric acid, silicone resin and organic solvent, and then dried to obtain mechanically crushed FeSiAl insulating powder. The mass percentage of the FeSiAl mechanical crushing powder in the total mass of the mixed solution including phosphoric acid, silicone resin and organic solvent is 95.5%.
[0101] The mechanically crushed FeSiAl insulation powder obtained after insulation coating is mixed with the demoulding lubricant and then pressed into shape; the amount of demoulding lubricant used is 0.4% of the amount of mechanically crushed FeSiAl insulation powder used. The pressing force for pressing is 20t / cm 2 The outer diameter of the pressed magnetic powder core is 26.9 mm, the inner diameter is 14.7 mm, and the height is 11.2 mm.
[0102] After pressing and forming, the magnetic powder core is subjected to stress relief annealing at a temperature of 700°C for 40 minutes to obtain a Sendust magnetic powder core, and the magnetic core performance is tested.
[0103] The sendust magnetic powder cores of the above-mentioned embodiments 1-4 and comparative examples 1-2 were respectively tested for magnetic core performance, and the test methods were as follows: the magnetic core was tested for density by the drainage method; the inductance of 0A and the bias inductance at 100 Oe were tested by an LCR tester (Microtest 6632+6240), the number of winding turns was 25, the test conditions were 1V, 100kHz, and the magnetic permeability and DC-Bias (100 Oe) were calculated; Pcv was tested by a BH tester (SY-8218), and the electronic wire was double-wound with 20 turns. The test results are shown in Table 1 below.
[0104] Table 1
[0105] It can be seen from the comparison results of Examples 1-2 and Comparative Example 2 in Table 1 that, compared with the crushed FeSiAl powder purchased from the market, the surface of the Sendust magnetic powder core prepared from the spherical FeSiAl powder of the present invention is smooth and has no sharp corners, and the magnetic core density is increased by 3%-5%, and the magnetic core loss and DC superposition characteristics are improved. Furthermore, it can be seen from the results of Examples 1-4 that the magnetic core performance of the Sendust magnetic powder core prepared by mixing the spherical FeSiAl and the atomized spherical FeSiAl powder in a certain proportion is further improved, and the characteristics of the Sendust magnetic powder core prepared from the atomized spherical FeSiAl powder in Comparative Example 1 are equivalent, which can reduce the cost of raw materials.
[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A Sendust magnetic powder core, characterized in that: The sendust magnetic powder core is prepared from raw materials including spherical FeSiAl powder, and the spherical FeSiAl powder is prepared by atomizing powder on a 200-mesh sieve; the composition of the spherical FeSiAl powder is Fe 100-a-b Si a Al b , wherein 8.5≤a≤9.9, 5.0≤b≤6.0, a and b respectively represent the mass percentage of the corresponding components; the grain size of the spherical FeSiAl powder is 10-30μm.
2. The Sendust magnetic powder core according to claim 1, characterized in that: The spherical FeSiAl powder is formed by a plurality of polyhedral crystal grains similar to pomegranate seeds being tightly combined, and has a smooth cross section without sharp corners.
3. The Sendust magnetic powder core according to claim 1, characterized in that: The raw materials for preparation also include spherical FeSiAl powder, wherein the spherical FeSiAl powder is a powder under a 200-mesh sieve by gas atomization, and D50 is 30-40 μm; Preferably, the composition of the spherical FeSiAl powder is consistent with the composition of the quasi-spherical FeSiAl powder; Preferably, the amount of the quasi-spherical FeSiAl powder is 30%-50% of the sum of the amounts of the quasi-spherical FeSiAl powder and the spherical FeSiAl powder.
4. The Sendust magnetic powder core according to claim 1, characterized in that: The magnetic core density of the Sendust magnetic powder core is 5.90-6.25 g / cm 3 ; The magnetic permeability of the Sendust magnetic powder core is 58-62H / m.
5. A Sendust magnetic powder core, characterized in that: The sendust magnetic powder core is prepared from raw materials including spherical FeSiAl powder, wherein the spherical FeSiAl powder is formed by a plurality of polyhedral grains similar to pomegranate seeds being tightly combined, and has a smooth cross section without sharp corners.
6. The Sendust magnetic powder core according to claim 5, characterized in that: The spherical FeSiAl powder is prepared by atomizing powder on a 200-mesh sieve; the composition of the spherical FeSiAl powder is Fe 100-a-b Si a Al b , wherein 8.5≤a≤9.9, 5.0≤b≤6.0, a and b respectively represent the mass percentage of the corresponding components; the grain size of the spherical FeSiAl powder is 10-30μm.
7. The Sendust magnetic powder core according to claim 6, characterized in that: The raw materials for preparation also include spherical FeSiAl powder, wherein the spherical FeSiAl powder is a powder under a 200-mesh sieve by gas atomization, and D50 is 30-40 μm; Preferably, the composition of the spherical FeSiAl powder is consistent with the composition of the quasi-spherical FeSiAl powder; Preferably, the amount of the quasi-spherical FeSiAl powder is 30%-50% of the sum of the amounts of the quasi-spherical FeSiAl powder and the spherical FeSiAl powder.
8. The Sendust magnetic powder core according to claim 6, characterized in that: The magnetic core density of the Sendust magnetic powder core is 5.90-6.25 g / cm 3 ; The magnetic permeability of the Sendust magnetic powder core is 58-62H / m.
9. The method for preparing the Sendust magnetic powder core according to any one of claims 1 to 4 or the Sendust magnetic powder core according to any one of claims 5 to 8, characterized in that: The steps include: The powder on the atomized 200-mesh sieve is mechanically crushed and passed through a 200-mesh sieve to obtain spherical FeSiAl powder; The obtained quasi-spherical FeSiAl powder is subjected to insulation coating, compression molding and stress annealing in sequence to obtain a Sendust magnetic powder core.
10. The preparation method according to claim 9, characterized in that: The insulating coating comprises: uniformly mixing the quasi-spherical FeSiAl powder with a mixed solution comprising phosphoric acid, silicone resin and an organic solvent, and then drying to obtain the quasi-spherical FeSiAl insulating powder; Preferably, in the mixed solution, the weight ratio of phosphoric acid, silicone resin and organic solvent is (0.5-1): (0.2-0.5): (2-3); Preferably, the mass percentage of the quasi-spherical FeSiAl powder to the total mass of the quasi-spherical FeSiAl powder and the mixed liquid is 94%-96.5%; Preferably, the spherical FeSiAl insulating powder obtained after insulation coating is mixed evenly with a demoulding lubricant and then pressed into shape; more preferably, the amount of the demoulding lubricant is 0.2%-0.4% of the amount of the spherical FeSiAl insulating powder.
11. The preparation method according to claim 10, characterized in that: The sendust magnetic powder core also includes spherical FeSiAl powder, and the insulating coating includes: uniformly mixing the quasi-spherical FeSiAl powder with a mixed solution including phosphoric acid, silicone resin and organic solvent, and then drying to obtain quasi-spherical FeSiAl insulating powder; uniformly mixing the spherical FeSiAl powder with a mixed solution including phosphoric acid, silicone resin and organic solvent, and then drying to obtain spherical FeSiAl insulating powder; Preferably, the mass percentage of the quasi-spherical FeSiAl powder to the total mass of the quasi-spherical FeSiAl powder and the mixed liquid is 94%-96.5%; the mass percentage of the spherical FeSiAl powder to the total mass of the spherical FeSiAl powder and the mixed liquid is 94%-96.5%; Preferably, the quasi-spherical FeSiAl insulating powder obtained after insulation coating and the spherical FeSiAl insulating powder are mixed evenly with a demolding lubricant and then pressed into shape; more preferably, the amount of the demolding lubricant is 0.2%-0.4% of the sum of the amounts of the quasi-spherical FeSiAl insulating powder and the spherical FeSiAl insulating powder.
12. The preparation method according to claim 9, characterized in that: The pressing force of the pressing molding is 20-22t / cm 2 The outer diameter of the pressed magnetic powder core is 25-30mm, the inner diameter is 14-15mm, and the height is 10-12mm; And / or, the stress annealing is performed at a temperature of 600-800° C. and for a time of 30-50 min.
